AURA (2024)
This thesis presents a proposal for playful tools designed to facilitate the understanding of the physical and emotional changes that girls between 8 and 10 years old experience during the menstrual cycle. These tools are especially adapted for girls who live in single-parent households headed by men. The methodology is based on experiential learning, using the narrative and rhetoric of the character to create interactive scenarios that explain in a clear and simple way the aspects of the menstrual cycle and how to address its symptoms..